Births in Times of Pandemic: Mothers’ Views on the Use of COVID-19 Hospital Precautionary Measures - Mena, Constanza; Cifuentes, Javier; Silva, Rosa; Lagos, Rodrigo; Díaz, Blanca; Palma, Elisa; Morales-Reyes, Irma; Olhaberry, Marcia; Ambiado, Sergio (Psykhe, 2025)
Due to the COVID-19 pandemic, health institutions adjusted protocols to include additional precautionary measures which may impact mothers’ and babies’ experiences of birth and post-partum. This mixed-methods cross-sectional study aims to describe mothers’ experience of hospital precautionary measures and their view on how these impacted on their levels of discomfort as well as positive and negative feelings experienced by them and their newborns, and maternal depressive symptomatology. A convenience sample from a private clinic in Santiago was used to compare two groups: 62 mothers with a negative Sars-CoV-2 PCR test (controls) and 58 mothers with a positive or pending Sars-CoV-2 PCR test prior to labor (cases), with different precautionary measures applied according to risk. An online questionnaire designed for this study and the EPDS was used. T-tests were used for comparing means as well as non-parametric tests and qualitative thematic analysis. Cases experienced more discomfort than controls, but at the same time they reported feeling significantly more competent. Of the total sample, 51.67% were at risk of postpartum depression, with no significant differences between groups. No significant differences were found in newborns’ level of discomfort, stress or positive or negative feelings according to mothers. Mothers reported an overall positive impact on their mother-infant bond. These results emphasize that mothers in their perinatal period have been exposed to a highly stressful context during the pandemic, which has impacted on their mental health. The impact of hospital precautionary measures, their implications for maternity protocols and these patients’ need for support are discussed.